Agritourism Product Development Plan : in Cigombong Agri-technopark, Bogor Regency - Wyratama, Marubeni Yusuf; Marsongko, Eka Paramita; Darwis, Riadi (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2024)
This research is focused on agritourism product development model in Cigombong Agri-technopark with emphasis on tourism product components which consist of physical product, packaging, program, and people. The agrotourism product components to be identified based on physical and non-physical condition. Descriptive qualitative method will be used with Interactive Model Analysis as the data analysis technique. Research summarized that the potential agritourism theme to be developed is modern agriculture. The targeted tourist segment are private tourist and educational institution. Recruiting for human resources require intensive training. Developing tour package requires substantial adjustment of the package based on the tourist’s demography.